Expedient Synthesis of Ubiquitin‐like Protein ISG15 Tools through Chemo‐Enzymatic Ligation Catalyzed by a Viral Protease Lbpro. Issue 40 (29th August 2022) - Wang, Tian; Li, Chuntong; Wang, Meijing; Zhang, Jiachen; Zheng, Qingyun; Liang, Lujun; Chu, Guochao; Tian, Xiaolin; Deng, Haiteng; He, Wei; Liu, Lei; Li, Jinghong
Abstract: Ubiquitin (Ub)‐like protein ISG15 (interferon‐stimulated gene 15) regulates innate immunity and links with the evasion of host response by viruses such as SARS‐CoV‐2. Dissecting ISGylation pathways recently received increasing attention which can inform related disease interventions, but such studies necessitate the preparation and development of various ISG15 protein tools. Here, we find that the leader protease (Lb pro ) encoded by foot‐and‐mouth disease virus can promote ligation reactions between recombinant ISG15 and synthetic glycyl compounds, generating protein tools such as ISG15‐propargylamide and ISG15‐rhodamine110, which are needed for cellular proteomic studies of deISGylases, and the screening and evaluation of inhibitors against SARS‐CoV‐2 papain‐like protease (PLpro). Furthermore, this strategy can be also used to load ISG15 onto the lysine of a synthetic peptide through an isopeptide bond, and prepare Ub and NEDD8 (ubiquitin‐like protein Nedd8) protein tools. Abstract : A protease (Lb pro ) from foot‐and‐mouth disease virus can ligate synthetic glycyl compounds to ISG15 (interferon‐stimulated gene 15), generating various ISG15 protein tools for cellular proteomic studies, as well as screening and evaluation of small molecules against SARS‐CoV‐2 papain‐like protease (PLpro). This strategy can also synthesize ISG15‐modified peptide and Ub (ubiquitin)/NEDD8 (ubiquitin‐like protein Nedd8) protein tools.